Qualitative Analysis of the Impact of Workload on Employees at PT Jasa Raharja Purwokerto Branch - Sari, Cinta Annastasya; Palupi, Majang (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to gain an in-depth understanding of employee workload and its impact on well-being and performance at PT Jasa Raharja Purwokerto Branch. The research employs a qualitative approach with a case study method, collecting data through interviews, observations, and documentation involving five informants from various job positions. The findings indicate that workload is driven by the high number of traffic accident cases, compounded by limited human resources and the continuous adaptation to evolving digital systems. These conditions lead to several consequences, including physical fatigue, work stress, and work-life imbalance, which ultimately affect employee performance. Although, in general, employees maintain optimal performance, one informant admitted that their performance occasionally declines due to time pressure and a high volume of work. Nevertheless, most employees continue to strive to maintain their performance by demonstrating discipline, responsibility, and strong commitment to delivering optimal public service. This study also highlights the importance of human resource management policies focused on employee well-being and workload distribution to ensure the quality of public services remains consistent.